Voluntary tourism as the best tourist destination for volunteer work, especially in the Corona-19 crisis Volunteering in the Corona crisis, Bahrain took as a model - et. al., May MuneerMjuli Ali, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Voluntary tourism is a new type of tourism that has begun to spread around the world in a way in which there is a lot of reservation about the nature of the perverted view of every charitable work that is intended to provide services of interest to individuals and societies. In this research paper, researchers will deal with volunteer tourism in our Arab and Gulf countries, and the State of Bahrain in particular. Conditions are a type of tourism, as they are unsafe tourism. Given the nature of the situation and the state the state is going through, or the place the volunteer goes to with his desire to play a humanitarian and relief role. But the voluntary tourism intended in this regard is the tourism in which individuals seek to go to places and regions through which they can spend their holidays, relax themselves, and spend their time in a useful work at the same time, by presenting their efforts, experiences and advice for a place, environment or society. Really needs these efforts, so they convey a positive image to peers about themselves and their societies, and help societies, environments and peoples that may need this intervention and a positive role. Volunteer tourism in the Gulf societies and the State of Bahrain is one of the new types of tourism that benefit the host countries from the experiences and energies of the volunteer youth. The youth also learn aspects of the world they do not know and develop the capabilities of education and reform, in addition to aspects of entertainment. There are hundreds of volunteer organizations and charities that take care of dozens of issues, from children's education to development and construction projects to animal welfare. The volunteer tourist only has to define his areas of interest and the period that he would like to spend in humanitarian service during his voluntary travel. Nobody knows in particular how volunteer tourism originated, but some believe that the establishment of former US President John F. Kennedy of the American peace forces that arose with the aim of helping the countries of the world in emergencies, natural disasters and crises, is the beginning of this trend to help others for nothing. Volunteer tourism developed in the nineties to the point that the specialized publication "Condi Nast Traveler" considered it one of the directions of future tourism. A new name was created for this type of tourism, which combines volunteerism and tourism, which is (Voluntourism). Companies such as Go Eco and Go Volunteering have also specialized in facilitating the tasks of travelers to volunteer to find suitable opportunities for them and make all the required arrangements.